1994
DOI: 10.1159/000204128
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Patients with Monoclonal Grammopathy of Undetermined Significance is Mandatory for a Reliable Use of lnterleukin-6 and Other Nonspecific Multiple Myeloma Serum Markers

Abstract: Serum levels of various immunochémical markers of clinical interest, as interleukin-6 (IL-6), C-reactive protein (CRP) and β2-microglobulin (β2M), were measured in sera from 98 subjects affected with monoclonal gammopathy of undetermined significance (MGUS; 80% of which bearing cancer too) and from 39 patients with multiple myeloma (MM). In addition, the ratio between serum IgG/IgA amounts (GAR) was also calculated in monoclonal gammopathies of IgG type. Consistent with our previous inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…In most published studies on paraproteinaemia the absence of clinical evidence for a haematological malignancy has been accepted as a de®nition of MGUS. Greco et al (1994) have already demonstrated the importance of clearly de®ning patients with MGUS because the presence of a solid tumour markedly in¯uenced the serum levels of IL-6, CRP and b2M in patients with paraproteinaemia who were diagnosed as`MGUS', which we also showed.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In most published studies on paraproteinaemia the absence of clinical evidence for a haematological malignancy has been accepted as a de®nition of MGUS. Greco et al (1994) have already demonstrated the importance of clearly de®ning patients with MGUS because the presence of a solid tumour markedly in¯uenced the serum levels of IL-6, CRP and b2M in patients with paraproteinaemia who were diagnosed as`MGUS', which we also showed.…”
Section: Discussionsupporting
confidence: 66%
“…The patients were either treatment-naive, had received treatment before or were undergoing treatment when serum IL-6 was measured. Secondly, cut-off values for the upper normal IL-6 level in serum were either not given (Brown et al, 1991;Thaler et al, 1994;Greco et al, 1994;Kyrtsonis et al, 1996) or ranged widely from 3´2 pg/ml (Pelliniemi et al, 1995) to 3300 pg/ml (Tienhaara et al, 1994). Each study reported a different range of values, even for normal controls (Table III).…”
Section: Discussionmentioning
confidence: 99%